ANALISIS KINERJA TURBIN UAP UNIT 3 BERDASARKAN PERFORMANCE TEST DI UNIT PELAKSANA PT.PLN (PERSERO) PEMBANGKITAN ASAM-ASAM - Mahaputra, Kemas Ronand (Universitas Lambung Mangkurat, 2021)
This study purpose to determine the performance of steam turbines Unit 3 of PT.PLN (Persero) Pembangkitan Asam-asam by comparing the results of the data obtained by each performance test. This research was carried out by taking data performance tests in 2012, 2017, 2018 and 2019 and then processing the data and obtaining turbine heat rate values and average turbine efficiency then comparing the values obtained in each year. The data taken is obtained from the rendal operation of PT.PLN (Persero) Pembangkitan Asam-asam, data variables taken are load, main steam temperature inlet, main steam pressure inlet, HP heater feed outlet temperature, HP heater outlet pressure, main steam flow. Temperature and pressure obtained are then searched for enthalpy values. The data obtained to calculate the value of the turbine heat rate and turbine efficiency on average per time from each performance test then averages the value of the turbine heat rate and turbine efficiency each time the data collection performance test is then compared with the data each year.The calculation of the turbine heat rate uses the heat & mass balance method by measuring the value of the incoming and outgoing fluid differences and comparing the load obtained, the efficiency of the turbine is obtained by dividing the energy of 1 kW with a turbine heat rate then multiplying by 100%. The average turbine heat rate calculation result for each performance test which is on May 23, 2012 is 2,701, October 27, 2017 is 3,136, September 5, 2018 is 3,005, May 21, 2019 is 3,113. The average turbine efficiency value on May 23, 2012 is 37.02%, October 27 2017 is 31.39%, September 5 2018 is 33.28%, May 21, 2019 is 32.12%. The performance of PT PLN (Persero) Pembangkit Asam-asam Implementing Unit Unit 3 has decreased from 2012 to 2019 which is 4.9%